The tornoceratid ammonoids from the Roteisenstein Formation of Dillenburg (Cephalopoda, Ammonoidea) - Korn, Dieter; Bockwinkel, Jürgen (European Journal of Taxonomy, 2022)
The ammonoids of the suborder Tornoceratina from the Middle to Late Devonian Red Ironstone Formation of the area around Dillenburg (eastern Rhenish Mountains) are revised, mainly based on historical collections stored in the Museum für Naturkunde, Berlin. The species Tornoceras typus (Sandberger & Sandberger, 1851), Tornoceras frechi Wedekind, 1918 and Epitornoceras mithracoides (Frech, 1888) are re-described based on the original material from the Red Ironstone. The new genus Lentitornoceras gen. nov. is proposed for the new species L. materni gen. et sp. nov.; the new genus Paucitornoceras gen. nov. is proposed with the type species Goniatites paucistriatus. Epitornoceras transmediterraneum sp. nov. is described from the Anti-Atlas of Morocco and compared with E. mithracoides.